2021
DOI: 10.2337/dc22-s008
|View full text |Cite
|
Sign up to set email alerts
|

8. Obesity and Weight Management for the Prevention and Treatment of Type 2 Diabetes:Standards of Medical Care in Diabetes—2022

Abstract: The American Diabetes Association (ADA) “Standards of Medical Care in Diabetes” includes the ADA’s current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee (https://doi.org/10.2337/dc22-SPPC), are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(97 citation statements)
references
References 133 publications
1
95
0
1
Order By: Relevance
“…Long-term observational studies have reported not only sustainable weight loss but also improvements in the metabolic profile after BS, especially in terms of glycemic and lipid metabolism [ 12 ]. There is strong evidence suggesting that compared to lifestyle intervention and pharmacotherapy, BS may result in superior glycemic control, often leading to the remission of diabetes, while reducing cardiovascular risk factors in patients with type 2 diabetes mellitus (T2DM) [ 13 , 14 ]. Studies including the SOS, STAMPEDE and CROSSROAD trials have demonstrated the effectiveness of BS in T2DM remission and prevention [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term observational studies have reported not only sustainable weight loss but also improvements in the metabolic profile after BS, especially in terms of glycemic and lipid metabolism [ 12 ]. There is strong evidence suggesting that compared to lifestyle intervention and pharmacotherapy, BS may result in superior glycemic control, often leading to the remission of diabetes, while reducing cardiovascular risk factors in patients with type 2 diabetes mellitus (T2DM) [ 13 , 14 ]. Studies including the SOS, STAMPEDE and CROSSROAD trials have demonstrated the effectiveness of BS in T2DM remission and prevention [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bariatric surgery should also be considered as a treatment option for adults with T2DM and a BMI of 30.0–34.9 who have inadequate glycemic control and cannot achieve sustainable weight loss despite lifestyle changes and optimal treatment. [ 13 , 14 , 18 ]. Additionally, BS is associated with both short- and long-term improvement in dyslipidemia, as shown by the STAMPEDE trial, which reported reductions in triglyceride levels of 40% and 29% in the RYGB and VSG groups, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction can be compensated by adding exercise as it increases metabolic rate and energy expenditure [ 76 ]. Together diet and exercise can enhance weight loss and maintain it in the long-term [ 76 ]; this is the most recommended strategy to achieve weight loss in different metabolic diseases guidelines [ 11 , 77 ]. Contrary to this, there are some studies sustaining that exercise may not enhance weight loss but gives other important benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The marked growth of the dual epidemics of type 2 diabetes and obesity contributes directly to the increasing prevalence of cardiovascular disease (CVD) and represents one of the most important public health challenges worldwide. 1 , 2 , 3 , 4 Weight loss with intensive lifestyle intervention (ILI) has become a standard recommendation in the guidelines for the management of individuals with type 2 diabetes and comorbid obesity 5 ; however, the level of evidence for such recommendations is only in “class B” because the evidence provided by randomized studies is limited. 5 The Look AHEAD (Action for Health in Diabetes) trial, 6 the largest trial to date of an ILI for adults with overweight/obesity and type 2 diabetes, did not show a significant reduction in cardiovascular morbidity or mortality.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 Weight loss with intensive lifestyle intervention (ILI) has become a standard recommendation in the guidelines for the management of individuals with type 2 diabetes and comorbid obesity 5 ; however, the level of evidence for such recommendations is only in “class B” because the evidence provided by randomized studies is limited. 5 The Look AHEAD (Action for Health in Diabetes) trial, 6 the largest trial to date of an ILI for adults with overweight/obesity and type 2 diabetes, did not show a significant reduction in cardiovascular morbidity or mortality. Of note, although the majority of the participants in the intervention group (55·1%) had achieved the study weight loss goal (Loss of ≥7% of baseline weight) at year 1, 7 they had not maintained this weight loss at the end of the trial due to weight regain.…”
Section: Introductionmentioning
confidence: 99%